Seipin regulates ER–lipid droplet contacts and cargo delivery. (22nd November 2016) - Salo, Veijo T; Belevich, Ilya; Li, Shiqian; Karhinen, Leena; Vihinen, Helena; Vigouroux, Corinne; Magré, Jocelyne; Thiele, Christoph; Hölttä‐Vuori, Maarit; Jokitalo, Eija; Ikonen, Elina
Abstract: Seipin is an endoplasmic reticulum (ER) membrane protein implicated in lipid droplet (LD) biogenesis and mutated in severe congenital lipodystrophy (BSCL2). Here, we show that seipin is stably associated with nascent ER–LD contacts in human cells, typically via one mobile focal point per LD. Seipin appears critical for such contacts since ER–LD contacts were completely missing or morphologically aberrant in seipin knockout and BSCL2 patient cells. In parallel, LD mobility was increased and protein delivery from the ER to LDs to promote LD growth was decreased. Moreover, while growing LDs normally acquire lipid and protein constituents from the ER, this process was compromised in seipin‐deficient cells. In the absence of seipin, the initial synthesis of neutral lipids from exogenous fatty acid was normal, but fatty acid incorporation into neutral lipids in cells with pre‐existing LDs was impaired. Together, our data suggest that seipin helps to connect newly formed LDs to the ER and that by stabilizing ER–LD contacts seipin facilitates the incorporation of protein and lipid cargo into growing LDs in human cells. Synopsis: Seipin, mutated in severe congenital lipodystrophy (BSCL2), is an ER–lipid droplet (LD) contact protein that regulates the extent of ER–LD contacts and facilitates incorporation of lipid and protein cargo into maturing LDs. Seipin deficiency increases the heterogeneity of ER–LD contacts, resulting in completely missing, rudimentary, or very extensive contacts. Seipin is required during LD formation for the targeting of ER‐derived fatty acid‐activating enzyme ACSL3 to LDs. An ER‐to‐LD targeting model peptide and a fluorescent fatty acid analog initially reach newly formed LDs, but their subsequent incorporation into LDs is impaired in the absence of seipin. In seipin deficiency, the fatty acid flux to neutral lipids becomes compromised when LD formation has been initiated. Abstract : Seipin, mutated in severe congenital lipodystrophy (BSCL2), is an ER–lipid droplet (LD) contact protein that regulates the extent of ER–LD contacts and facilitates incorporation of lipid and protein cargo into maturing LDs.